IMPROVE DIALOG CATEGORIZATION OF THE METHODS FOR RISK ASSESSMENT OF ЕNVIRONMENTAL DANGER ECONOMICAL ACTIVITIES: IMPROVE DIALOG CATEGORIZATION OF THE METHODS FOR RISK ASSESSMENT OF ЕNVIRONMENTAL DANGER ECONOMICAL ACTIVITIES - Vladimirov, Lyubomir; Hristova Кrassimira (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The purpose of this work is to propose an advanced categorization of methods for risk assessment of environmentally hazardous sites that will help the consumers. To achieve it three tasks are solved: 1. Defining features of categorization methods; 2. Classification of methods for risk assessment; 3. Compilation of a catalog, which allows easy and proper choice of methods for analysis of environmental risk and application in solving practical problems.